Long Run Equilibrium Relationship Between Money and Prices in Selected Asian Countries - Noor Azlan Ghazali,; Shamsubaridah Ramlee, (Asian Academy of Management Journal, 2001)
The Monetarist proposition of the relationship between the growth of money and changes in prices is investigated for eight selected Asian counties (Bangladesh, India, Indonesia, Malaysia, Pakistan, Singapore and Thailand). Specifically, the long run equilibrium relationship between growth of money stock and changes in prices is examined based on three framework of analysis ; cointegration analysis, error correction model and impulse response functions of a vector autoregression analysis (VAR). The results are in favour of the Monestarist proposition. Money growth and changes in prices are shown to be cointegrated in all countries. Movement in changes in prices is subject to its deviation from long run equilibrium path determined by growth in monetary aggregate. The speed of adjustment of prices towards its long run equilibrium path and the explanatory power of growth of monetary aggregate in explaining inflation remain regardless of the measures of money employed. The impact of changes in money on prices is permanent and significant. Reactions of prices are immediate in India, Indonesia, Malaysia and Thailand but delayed in other countries. It begins to occurs after toward its long run equilibrium is significant in all countries with Bangladesh recording the highest speed of adjustment of near to complete correction. The evidence presented highlights the importance of domestic monetary controls in managing inflation in each of these countries, Monetarism is alive and valid in these developing nations of Asia.